Amauroderma trichodermatum (ganodermataceae, basidiomycota) : first record from Bolivia and geographic distribution map, with notes on nomenclature and morphology - Newman, Daniel S. (2015)
Fil: Robledo, Gerardo L. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas Físicas y Naturales. Instituto Multidisciplinario de Biología Vegetal. Instituto Multidisciplinario de Biología Vegetal; Argentina.